Comparative analysis of schooling situations using longitudinal data: improving enrollment patterns of individual children in Honduras. Issue 4 (26th August 2021) - Ashida, Akemi
Abstract : Purpose: This longitudinal study aims to understand the circumstances of and changes in student enrollment in Honduras by comparing geographically and socioeconomically different areas and students' year of school entrance. Design/methodology/approach: The sample was made up of 4, 043 students from seven primary schools in a regional city and the capital city. Students' enrollment patterns, schooling and trajectories from entrance to departure, whether as a result of graduating or dropping out, were examined. Findings: The number of students who graduated without repetition increased, and most of the students accessed primary education at the official entrance age. However, grade repetitions and dropouts were observed in the regional city in particular, and differences were also found in the school departure age by region. In the regional city, continuation of schooling after a change in residence has become more common in recent years. Adopting an automatic promotion policy could be one strategy for reducing grade repetitions and dropouts; however, further discussion is required to prepare a remedial opportunity for students who might otherwise lack the minimum proficiency level. Originality/value: Few studies have examined changes in school enrollment in Honduras from a micro perspective. This study contributes a practical approach to exploring educational trends in the region by explaining how students reached their final grades by tracking trajectories, which has not been observed so far in terms of the accumulated average.